2010
DOI: 10.1161/circep.109.924985
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Atrial Endothelin-1 With Atrial Rhythm, Size, and Fibrosis in Patients With Structural Heart Disease

Abstract: Background-Atrial fibrillation (AF) promotes atrial remodeling and can develop secondary to heart failure or mitral valve disease. Cardiac endothelin-1 (ET-1) expression responds to wall stress and can promote myocyte hypertrophy and interstitial fibrosis. We tested the hypothesis that atrial ET-1 is elevated in AF and is associated with AF persistence. Methods and Results-Left atrial appendage tissue was studied from coronary artery bypass graft, valve repair, and/or Maze procedure in patients in sinus rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 34 publications
8
105
1
1
Order By: Relevance
“…Angiotensin II and endothelin-1 are linked to inflammatory and proarrhythmogenic atrial remodelling. 2,[264][265][266] This evidence suggests that inflammatory cell infiltration has an important role in promoting the creation of a substrate for AF, as a result of conduction heterogeneity and slowing, both in the setting of cardiac surgery and beyond.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…Angiotensin II and endothelin-1 are linked to inflammatory and proarrhythmogenic atrial remodelling. 2,[264][265][266] This evidence suggests that inflammatory cell infiltration has an important role in promoting the creation of a substrate for AF, as a result of conduction heterogeneity and slowing, both in the setting of cardiac surgery and beyond.…”
Section: Impact Of Atrial Cardiomyopathies On Occurrence Of Atrial Fimentioning
confidence: 99%
“…However, expression of cardiac alpha-actin isotypes 1 and 2, tropomyosin alpha-and beta-chains, and myosin light chain embryonic muscle/atrial isoform in LAA from AF patients was found increased when compared to those from SR patients [24]. Another potential contributor to atrial remodelling, cardiac endothelin-1 (ET-1), is expressed as a response to wall stress and can promote myocyte hypertrophy and interstitial fibrosis [25]. Elevated atrial ET-1 level is been found associated with increased LA size, AF prevalence, hypertension, and heart failure [25].…”
Section: Markers Of Left Atrial Appendage Functionmentioning
confidence: 99%
“…Another potential contributor to atrial remodelling, cardiac endothelin-1 (ET-1), is expressed as a response to wall stress and can promote myocyte hypertrophy and interstitial fibrosis [25]. Elevated atrial ET-1 level is been found associated with increased LA size, AF prevalence, hypertension, and heart failure [25]. An association between ET-1 and atrial dilatation, fibrosis, and hypertrophy is been reported.…”
Section: Markers Of Left Atrial Appendage Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последующих работах была показана активация эндотелиновой системы у больных с тяжелой ХСН, маркером чего явилось повыше-ние плазменного уровня ЭТ и его предшествен-ника (Big-ET) [24,25]. При этом не было отмечено статистически достоверной связи между уровнем ЭТ-1 и Big-ET с этиологией сердечной недоста-точности [26]. Следует подчеркнуть, что достовер-ное повышение ЭТ и его предше ственника у здо-ровых людей, пациентов с бессимптомной дис-функцией ЛЖ и начальными стадиями сердечной недостаточности выявлено не было [6].…”
unclassified